Socrates and philosophy in the dialogues of Plato - Peterson, Sandra, 1940- (Cambridge ; Cambridge University Press, 2011)
'In Plato's Apology, Socrates says he spent his life examining and questioning people on how best to live, while avowing that he himself knows nothing important. Elsewhere, however, for example in Plato's Republic, Plato's Socrates presents radical and grandiose theses. In this book Sandra Peterson offers a new hypothesis which explains the puzzle of Socrates' two contrasting manners. She argues that the apparently confident doctrinal Socrates is in fact conducting the first step of an examination: by eliciting his interlocutors' reactions, his apparently doctrinal lectures reveal what his interlocutors believe is the best way to live. She tests her hypothesis by close reading of passages in the Theaetetus, Republic and Phaedo. Her provocative conclusion, that there is a single Socrates whose conception and practice of philosophy remain the same throughout the dialogues, will be of interest to a wide range of readers in ancient philosophy and classics'--
'The Socrates of some of Plato's dialogues is the avowedly ignorant figure of the Apology who knows nothing important and who gave his life to examining himself and others. In contrast, the Socrates of other dialogues such as the Republic and Phaedo gives confident lectures on topics of which the examining Socrates of the Apology professed ignorance. It is a longstanding puzzle why Socrates acts so differently in different dialogues. To explain the two different manners of Socrates a current widely accepted interpretation of Plato's dialogues offers this two-part, Platocentered, hypothesis: (i) the character Socrates, of the dialogues is always Plato's device for presenting Plato's own views; and (ii) Plato had different views at different times. The Socrates who confidently lectures presents these famous four doctrines: Plato's blueprint for the best state, Plato's'Theory of Forms,' Plato's view that philosophy is the knowledge of those Forms that fits the knower for the highest government stations, and Plato's arguments for the immortality of the soul'--
1. Opposed hypotheses about Plato's dialogues -- 2. Socrates in the Apology -- 3. Socrates in the digression of the Theaetetus: extraction by declaration -- 4. Socrates in the Republic, part I: speech and counter-speech -- 5. Socrates in the Republic, part II: philosophers, forms, Glaucon and Adeimantus -- 6. Socrates in the Phaedo: another persuasion assignment -- 7. Others' conceptions of philosophy in Euthydemus, Lovers, and Sophist -- 8. Socrates and Plato in Plato's dialogues -- 9. Socrates and philosophy.
Includes bibliographical references (p. 262-276) and indexes.
Keywords: Plato; Socrates; Philosophy